2004
DOI: 10.1097/00129492-200411000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Mechanical Performance of Ossiculoplasty Using a Prosthetic Malleus-to-Stapes Head with a Tympanic Membrane-to-Stapes Head Assembly in a Human Cadaveric Middle Ear Model

Abstract: Tension has a significant effect on prosthesis function. Malleus assembly to the stapes head type prostheses generally result in better transmission of vibrations to the stapes footplate than tympanic membrane assembly to the stapes head type prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 15 publications
4
38
1
Order By: Relevance
“…It has been long known that there is an impedance mismatch involved with this transfer of energy from air to fluid, with only 0.1% of acoustic energy traveling through air actually transferring into a water medium [13]. The middle ear in classic descriptions functions as an impedance matching device through three major mechanisms: a hydraulic lever, ossicular lever, and catenary lever [14]. The hydraulic lever concentrates acoustic energy at the oval window and results from the 17-to 20-fold difference in vibratory surface of the tympanic membrane compared with the smaller area of the stapes footplate [15].…”
Section: Middle Ear Structure and Physiologymentioning
confidence: 99%
“…It has been long known that there is an impedance mismatch involved with this transfer of energy from air to fluid, with only 0.1% of acoustic energy traveling through air actually transferring into a water medium [13]. The middle ear in classic descriptions functions as an impedance matching device through three major mechanisms: a hydraulic lever, ossicular lever, and catenary lever [14]. The hydraulic lever concentrates acoustic energy at the oval window and results from the 17-to 20-fold difference in vibratory surface of the tympanic membrane compared with the smaller area of the stapes footplate [15].…”
Section: Middle Ear Structure and Physiologymentioning
confidence: 99%
“…The vertical placement of the prosthesis is a favorable position for a better hearing outcome [11] . Bance et al [9] reported the angulation of the prosthesis decreased the force transmission and better hearing outcomes of the MASH group on cadavers. Sacrificing the tensor timpani muscle to lateralize the malleus may help place the prosthesis in a proper vertical position, but it is vital to detect sufficient malleus stability.…”
Section: Discussionmentioning
confidence: 99%
“…PORPs are some of the most common tools available for otologists. Bance et al [9] first reported that the malleus to stapes assembly showed a better vibration transmission than the TM to stapes on cadaver temporal bone models and significantly related with tension. Since then, different studies have clinically shown that the preservation of the malleus maintains better hearing outcomes [6] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations